INFLUENCE OF HEALTH EDUCATION ABOUT SEX AND ITS IMPACT ON KNOWLEDGE OF PRIMARY PREVENTION OF SEXUAL VIOLENCE AMONG SCHOOL CHILDREN IN SDN BANGSAL 4, KEDIRI CITY - Sutik; Maria Anita Y.; Erva Elli Kristanti; Yoyok Febrijanto (Indonesian Health Literacy Journal, 2024)
Violence and sexual crimes that occur against children are problems that are still a global challenge and threat, including Indonesia. Because the resulting impact can damage the child's future both from physical, mental, social, psychological aspects, as well as the child's mindset. Sexual violence against children is one of the factors that has a negative influence on children's growth and development. This research studied the influence of education about sex and its impact on knowledge of primary prevention of sexual violence in children at SDN Bangsal 4, Kediri City. The research design used a comparative analytical design with a pre-post-test approach (One Group Pre-Test Post-Test Design), the sample size was 26 respondents were taken using total sampling technique. The independent variable in this research is education about sex and its impacts. Meanwhile, the dependent variable is knowledge of primary prevention of sexual violence in children. Data collection using a questionnaire. Data analysis used the Wilcoxon statistical test with a significance level of p<0.05. The results of the research showed that the level of knowledge after being given the intervention, the majority of respondents had good knowledge: 21 children (81%), and only a small portion had poor knowledge: 1 child (4%), and there was an influence of education about sex and its impact on primary prevention of sexual violence in children (Wilcoxon p value 0.000 < 0.05, then Ho is rejected). It was concluded that providing education about sex and its impact has a great influence on children's knowledge. Thus, it is hoped that through continuous education we can detect and minimize the number of incidents of sexual violence.